Sounding Automation Prototype in Storage Tank Model Based On Arduino Uno - Ahmad Mahfud; Istianto Budhi Rahardja; Muh Amran (Journal of Applied Sciences and Advanced Technology, 2019)
Sounding is the process of measuring and calculating a product to find out the amount. In the process of CPO sounding, measurements are made of the temperature of the oil in the storage tank. Storage tank is a tank used to store crude palm oil (CPO) produced before shipping. Sounding crude palm oil is an oil measurement process that includes the measurement of CPO levels and temperatures as an item to get the mass of CPO (kg CPO). The process of measuring the volume of oil is done using a sounding meter dipped in CPO in a storage tank to the measuring table. Temperature measurements are carried out using a thermometer that is inserted into a storage tank. In conditions on the ground that the measurement of the storage tank or storage tank is done manually to calculate the tank volume and there are many weaknesses. In this study, we will describe the sounding technique or measure the volume of oil in a storage tank by means of automation, where the automation system is designed with the aim of being able to carry out the measurement process on the storage tank in an automatic way. The results of this study can be concluded that measurements on storage tanks can be done automatically with the help of the HC-SR04 proximity sensor, thermocouple sensor, flow meter sensor and Arduino UNO which are passed on to laptops and gadgets, where based on the results of the experiments carried out the percentage of accuracy is obtained each sensor starts from the proximity sensor with 99.98%, temperature sensor 99.47% and flow meter sensor 99.88%.